När Policy Möter Verklighet - En analys av socialarbetares erfarenheter av hemlöshet, insatser och implementering - Disch,William; Joas,Lisa (2024)
This bachelor’s thesis explores social workers' experiences with two different approaches to addressing homelessness in Sweden: the Housing Ladder and Housing First. The study employs a qualitative research methodology, utilizing semi-structured interviews with social workers who have experience with both models. The analysis combines thematic coding with Fairclough's Critical Discourse Analysis (CDA) to examine how neoliberal discourse influences social workers' perceptions of homelessness and their professional practices. The study highlights the challenges and opportunities in phasing out the Housing Ladder and implementing Housing First as a long-term solution. The Housing Ladder used to be characterized by strict rules and extensive controls and was often perceived by clients as invasive and with limited effectiveness. Our findings reveal that the Housing Ladder has adopted some Housing First principles and taken a more humane as well as relation-based approach. Our findings indicate that the Housing ladder today is less governed by strict rules; thus resolving the main criticism against the model. However, the Housing First model is presented as a more flexible and individualized alternative, but its implementation faces challenges, particularly due to prevailing discourses and structural barriers.
Keywords: implementation; de-implementation; homelessness; neoliberal discourse; Housing first; housing ladder